A lottery improves performance on a low-stakes test for males but not females. Issue 5 (3rd September 2018) - Cole, James S.; Bergin, David A.; Summers, Jessica
Abstract: The purpose of this study was to address the effectiveness of autonomy support and a lottery-based reward in enhancing test performance and test-taking motivation on a low-stakes test. Two hundred and forty-six university students were randomly assigned to three groups – lottery, autonomy support and control – and took a mathematics test. Students in the autonomy support and lottery group reported putting forth more test-taking effort than students in the control group. Males who were offered a chance at winning the financial reward scored almost 10 points higher on the exam compared to females. Results showed no significant difference in test scores for female students among groups, suggesting that neither intervention had an impact on females.